Sustainable development in the era of FinTech and artificial intelligence - Nieborak, Tomasz (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
The paper concerns sustainable development in the context of the dynamic changes currently occurring in financial markets, driven by the advancements of artificial intelligence (AI) and financial technology (FinTech) applications. Innovative financial mechanisms, such as intelligent investment algorithms, AI-based credit scoring, and automated advisory systems, can support the achievement of sustainable development goals by enabling more effective risk management, directing capital toward green projects, and enhancing financial inclusion. The importance of appropriate financial regulation is emphasized, including the role of regulatory sandboxes that allow innovations to be tested in a safe environment, particularly with regards to mitigating systemic risk. The author argues that while the integration of AI with the FinTech sector has the potential to create a more sustainable financial system, it requires the development of regulatory frameworks that support innovation while protecting the public interest.